PROBLEMS OF GEOPHYSICS AND FLUID DYNAMICS OF BLOCK-HIERARCHICAL LITHOSPHERIC STRUCTURE - PRODAIVODA, G.; BAISAROVYCH, I.; PRODAIVODA, T. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The methodological principles of geophysical diagnostics of block-hierarchical lithospheric structure geodynamics are under consideration. It is emphasised that the basic matter of geophysical diagnostics ought to be meso- and micro-levels of the structure and their dynamic fluid mode (regime). The energy dispersion in the lithosphere is accompanied by destruction of one dense blocks' packing and formation of a new dense packing of blocks.